evaluate f(-3) when f(x)= 4x[sqr(3-x)] 10/6/2013 | Hannah from Los Angeles, CA | 2 Answers | 0 Votes Mark favorite Subscribe Comment
Substitute (-3) into the equation f(-3)=4(-3)(√3-(-3)) f(-3)=-12(√3+3) ANSWER: f(-3)=-12√6 √6 cannot be simplified, therefore it remains in the answer. 10/6/2013 | Ciera C. Comment
Hi Hannah; If the equation is... f(x) we are evaluating x as x. In this circumstance... we are evaluating x as -3. Therefore... f(x)= 4x[sqr(3-x)] f(-3)=4(-3)[sqr(3--3)] f(-3)=-12[sqr(6)]=-12(2.45)=-29 10/6/2013 | Vivian L. Comment